Current advancements in therapeutic approaches in orthopedic surgery: a review of recent trends - Liang, Wenqing; Zhou, Chao; Bai, Juqin; Zhang, Hongwei; Jiang, Bo; Wang, Jiangwei; Fu, Lifeng; Long, Hengguo; Huang, Xiaogang; Zhao, Jiayi; Zhu, Haibing (Frontiers in Bioengineering and Biotechnology, 2024)
Recent advancements in orthopedic surgery have greatly improved the management of musculoskeletal disorders and injuries. This review discusses the latest therapeutic approaches that have emerged in orthopedics. We examine the use of regenerative medicine, including stem cell therapy and platelet-rich plasma (PRP) injections, to accelerate healing and promote tissue regeneration. Additionally, we explore the application of robotic-assisted surgery, which provides greater precision and accuracy during surgical procedures. We also delve into the emergence of personalized medicine, which tailors treatments to individual patients based on their unique genetic and environmental factors. Furthermore, we discuss telemedicine and remote patient monitoring as methods for improving patient outcomes and reducing healthcare costs. Finally, we examine the growing interest in using artificial intelligence and machine learning in orthopedics, particularly in diagnosis and treatment planning. Overall, these advancements in therapeutic approaches have significantly improved patient outcomes, reduced recovery times, and enhanced the overall quality of care in orthopedic surgery.